PENGEMBANGAN MODUL PEMBELAJARAN BIOLOGI BERORIENTASI PENDEKATAN KONSEP DILENGKAPI PETA PIKIRAN UNTUK SMP KELAS VIII PADA MATERI SISTEM DALAM KEHIDUPAN TUMBUHAN - Eza, Gita Noveri; Efi, Agusti; Lufri, Lufri (Kolaboratif, 2014)
Teacher as one of component in learning plays an important role to create a learning process such that students can understand the learning well. One way in presenting the material is by using module which is appropriate with students’ characteristics. Through module, students can learn based on their own ability in learning. Module can be used for biology lesson. To facilitate students in understanding the biology lesson which is rich in concept, it takes an approach that focuses on emphasizing the learning concepts, namely concept approach. It is intended to avoid misconceptions of the learners. For all concepts can be mastered by the learner as a whole, it is needed a media summarizing all the material so that it can help students memorize key concepts, namely mind map. The result of study is description of the concept approach-oriented biology lesson modules completed with mind map for 8th grade of Junior High School at the system of plant life.